UPAYA GURU PAI DALAM MENANAMKAN NILAI AKHLAK MULIA PADA SISWA DI ERA DIGITAL - Wardah Febrianas Ula; Rismatul Khusnia (JURNAL ILMIAH NUSANTARA, 2025)
The digital era has a significant impact on students' lives, including in terms of character and moral formation. This article discusses the efforts made by Islamic Religious Education (PAI) teachers in instilling noble moral values amidst the challenges of the digital age. Through a descriptive quantitative approach, this study examines learning strategies, the use of technology, and the role of teachers as role models in guiding students. The results of the study indicate that PAI teachers need to integrate digital media wisely, build effective communication with students, and instill moral values through habituation and role models. Thus, PAI teachers have a strategic role in maintaining students' morality so that it remains in line with Islamic teachings even though they are in the midst of rapid technological developments.